The Effect Of The Implementation Of The Principles Of Good Corporate Governance On Conceptual Value For Money Businesses In Ascrindo Companies - Fitra Nurhakim; Sri Lestari (SEIKO : Journal of Management & Business, 2023)
The implementation of good corporate governance is one of the important factors for the company in carrying out its activities. This is realized by the integrity and professional service in every activity and becomes the Corporate Culture that is always cared for by all the people of Askrindo, so that the Company is able to grow and have a high competitiveness, as well as creating added value for stakeholders that should be reviewed from the effectiveness of employee performance and the impact of such performance should be analyzed through structured measurement. The researchers formulated questions on the impact of the principles of Good Corporate Governance on employees with the aim of measuring performance in the company. The research method used is quantitative which will draw data from the field and be analyzed as a benchmark for the impact of the principles of Good Corporate Governance on employee performance. The results of this study are achieved indicators of success or a better level of performance by demonstrating on indicators such as: economy, efficiency, effectiveness and outcome. Keywords: Good Corporate Governance